Pengaruh Brand Image Dan Kualitas Produk Terhadap Minat Beli Ulang Mixue - Safitri, Rani; Indrawati, Henny; Isjoni, M. Yogi Riyantama (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The aim of this study was to determine the effect of brand image and product quality on Mixue's repurchase intention. The research population is all Mixue consumers whose numbers are unknown. The research sample was 100 respondents. The sampling technique used purposive sampling with sample criteria at least 3 times making a purchase. Data obtained by distributing questionnaires directly. The data was analyzed by multiple linear regression. The results showed that brand image and product quality simultaneously affect repurchase intention. Brand image has no effect on repurchase intention. Product quality has a positive and significant effect on repurchase intention. The better the quality of Mixue products, the more interest in repurchasing Mixue products will increase.